Reflecting on Disinformation of Covid-19: Action Research on Undergraduate Students' Transformed Practices of Critical Framing Design - Tzong-Sheng Deng (National Taipei University of Education, 2021)
Social media spreads risk awareness about COVID-19. This study aimed to explore the experience of a college professor in incorporating media multiliteracies, reflecting teaching and learning as well as interpret how to make connections between social media and in-class activities during creations. Applying action research as the research method, twenty-three undergraduate students who took "media ethics" class participated in the study, with eight works created. The results show that students identified themes of familiar misinformation as mission, transforming them into a form of reflective creation. Students could communicate the reflective disinformation on COVID-19 through sharing of redesigned messages on social media beyond the classroom. For educators, social media might foster a participatory and creative environment that allows for exchange of information and creation of new networks and organizations, thereby providing a creative educational space for discussing topics related to disasters and pandemics. Creations involving controversial COVID-19 disinformation helped students develop critical thinking and science media literacy. Moreover, students developed the ability to apply multiliteracy in daily life and share their reflections with others. The contribution of this study shows that multiliteracies as mediums indeed helped the learners raise art-based learning skills and cross-disciplinary understanding, and the teacher and students were provided opportunities to improve their professional knowledge and competence about reflective information in a co-create process. Based on these contributions, some suggestions were proposed for further art-based cross-disciplinary education research.